Gli scavi dell’Università di Napoli L’Orientale nel villaggio pre-ellenico e nell’abitato greco-romano di Cuma: le campagne del 2024 e del 2025 - D'Acunto, Matteo; Capurro, Marco; Improta, Chiara; Merluzzo, Cristiana; Nitti, Francesco; Soldatini, Mara (Archeologie tra Oriente e Occidente, 2025)
This paper outlines the results of the 2024 and 2025 excavation campaigns conducted by the University of Naples L’Orientale in Cumae in the Pre-Hellenic village and the Greek-Roman city, in the area north of the Forum Baths. In particular, it presents the excavation of a Pre-Hellenic hut with related finds (780-750 BC), a street whose phases are important to define the transformation in the urban layout of the district from the Greek to the Roman periods, and a Roman-era metalworking workshop.